Composite Leading Indicators der amerikanischen Wirtschaft - Prognosegüte des Conference Board und des OECD Ansatzes im Vergleich - Marian Berneburg (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2003)
– The Paper analyses both the Conference Board as well as the OECD Leading Indicators concerning their forecasting properties of overall economic activity. For this purpose the two indicators are introduced separately and several in-sample and out-of-sample tests are being conducted. The main focus, apart from other methods, is being laid on coherence tests as well as the Diebold/Mariano test. In contrast to many other analyses dealing with this topic, the chosen reference series is not industrial production, but rather the coincident index, as reported by the conference board. It seems as if both indicators show some sign of correlation to overall economic activity, but at the same time fail to improve on the forecasts of a simple time series model.
urn:nbn:de:gbv:3:2-20374
Keywords: 330; Konjunkturindikator; Konjunkturprognose; Prognoseverfahren; Statistischer Test; Vergleich; USA; OECD-Staaten